The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/md.0000000000014697
|View full text |Cite
|
Sign up to set email alerts
|

Early characteristics of fulminant myocarditis vs non-fulminant myocarditis

Abstract: Background: Fulminant myocarditis (FM) is a sub-category myocarditis. Its primary characteristic is a rapidly progressive clinical course that necessitates hemodynamic support. FM can be difficult to predict at the onset of myocarditis. The aim of this meta-analysis was to identify the early characteristics in FM compared to those of non-fulminant myocarditis (NFM). Methods: We searched the databases of MEDLINE, EMBASE, CENTRAL, for studies comparing FM with acute NFM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
0
27
0
2
Order By: Relevance
“…The presence of wide QRS complex has been associated with a poorer prognosis, particularly in FM, where it can be one of the earliest clinical signs (Elamm et al, 2012;Ginsberg & Parrillo, 2013;Ukena et al, 2011;Wang et al, 2019). A study by Morgera B et al showed that abnormal QRS complexes were associated with more severe left ventricular impairment and with a higher frequency of hypertrophy and fibrosis (according to histologic examination) (Morgera et al, 1992).…”
Section: Q R S Comple Xmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of wide QRS complex has been associated with a poorer prognosis, particularly in FM, where it can be one of the earliest clinical signs (Elamm et al, 2012;Ginsberg & Parrillo, 2013;Ukena et al, 2011;Wang et al, 2019). A study by Morgera B et al showed that abnormal QRS complexes were associated with more severe left ventricular impairment and with a higher frequency of hypertrophy and fibrosis (according to histologic examination) (Morgera et al, 1992).…”
Section: Q R S Comple Xmentioning
confidence: 99%
“…ST depression is less frequent in myocarditis/myopericarditis (with the exception of lead aVR); when present in patients simultaneously displaying ST elevation, it likely represents a reciprocal change and suggests MI (Pollak & Brady, 2012). However, nonspecific ST depression has been reported in FM (Ginsberg & Parrillo, 2013), where it can represent one of the earliest clinical signs (Wang et al, 2019). Moreover, De Winter sign (defined as a 1-3 mm upsloping ST depression in V1-V6 that continues into tall, positive symmetrical T waves, generally associated with ST elevation of 1-2 mm in aVR lead and mild ST depression in inferior leads), a well-described ECG pattern that typically suggests acute occlusion of proximal left anterior descending coronary artery, has also been described in ACS-like myocarditis (de Winter, Verouden, Wellens, & Wilde, 2008;García-Izquierdo, Parra-Esteban, Mirelis, & Fernández-Lozano, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…It has been observed that the different components of electrocardiography (ECG) usually alter in myocarditis patients, such as prolonged PR interval, wide QRS complex, nonspecific ST-T changes, emergence of pathological Q wave [11]. Although many changes are not pathognomonic, a few features are more likely to occur in the FM than NFM [12][13][14][15]. Based on the above findings, we postulate that combination of the various alterations on the ECG might create an useful index for rapid diagnosis of the CS in acute myocarditis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with fulminant myocarditis require varying platforms of hemodynamic support (1). This group can be differentiated from the more benign uncomplicated myocarditis presentation as they have significantly lower systolic blood pressure, higher creatine kinase, wider QRS duration, lower left ventricular ejection fraction, thicker left ventricular posterior wall diameter, higher incidence of ST depression, and more ventricular tachycardia/ventricular fibrillation (1).…”
Section: Discussionmentioning
confidence: 99%